2023
DOI: 10.3390/plants12244176
|View full text |Cite
|
Sign up to set email alerts
|

Species Delimitation in a Polyploid Group of Iberian Jasione (Campanulaceae) Unveils Coherence between Cryptic Speciation and Biogeographical Regionalization

Miguel Serrano,
Santiago Ortiz

Abstract: Groups with morphological stasis are an interesting framework to address putative cryptic species that may be hidden behind traditional taxonomic treatments, particularly when distribution ranges suggest disjunct and environmentally heterogeneous biogeographic patterns. New hypotheses of delimitation of evolutionary independent units can lead to the identification of different biogeographic processes, laying the foundation to investigate their historical and ecological significance. Jasione is a plant genus wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“… Ranasinghe et al (2023) , Schattanek-Wiesmair et al (2024) ), although studies on a diverse array of organisms has shown ASAP to be one of the most reliable single-locus species delimitation methods (e.g. Muster et al (2021) , Serrano and Ortiz (2023) , Solovyeva et al (2023) , Yin et al (2023) , Schattanek-Wiesmair et al (2024) ). With very few molecular studies on Diplura including different populations of the same species, there is little information on the typical intraspecific genetic distances in Diplura .…”
Section: Discussionmentioning
confidence: 99%
“… Ranasinghe et al (2023) , Schattanek-Wiesmair et al (2024) ), although studies on a diverse array of organisms has shown ASAP to be one of the most reliable single-locus species delimitation methods (e.g. Muster et al (2021) , Serrano and Ortiz (2023) , Solovyeva et al (2023) , Yin et al (2023) , Schattanek-Wiesmair et al (2024) ). With very few molecular studies on Diplura including different populations of the same species, there is little information on the typical intraspecific genetic distances in Diplura .…”
Section: Discussionmentioning
confidence: 99%